2019
DOI: 10.1016/j.ymgmr.2019.100459
|View full text |Cite
|
Sign up to set email alerts
|

Emotional experience in parents of children with Zellweger spectrum disorders: A qualitative study

Abstract: Zellweger spectrum disorders (ZSDs) are rare, debilitating genetic diseases of peroxisome biogenesis that require constant management and lifelong care. Nevertheless, the experience of family caregivers for children diagnosed with ZSD is not well understood. In this study, we sought to characterize the emotional experience of ZSD family caregivers. Three 90-min focus groups were conducted with thirty-seven parents (25 mothers and 12 fathers) of children with ZSD during a family advocacy conference. Focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 23 publications
(32 reference statements)
1
52
0
7
Order By: Relevance
“…Specific for diseases usually emerging in childhood (neurofibromatosis type 1, Marfan syndrome) was parental behaviour perceived as overprotective and burden for patients’ parents. This is in line with other qualitative studies on parental experiences with paediatric rare diseases such as osteogenesis imperfecta,11 inherited metabolic diseases12 13 and Zellweger spectrum disorders14 from a caregivers’ perspective. In these studies, parents of affected children reported to experience concern, emotional stress and feelings of uncertainty and being overwhelmed, which stresses the need for support systems for caregivers of patients with paediatric rare diseases.…”
Section: Discussionsupporting
confidence: 89%
“…Specific for diseases usually emerging in childhood (neurofibromatosis type 1, Marfan syndrome) was parental behaviour perceived as overprotective and burden for patients’ parents. This is in line with other qualitative studies on parental experiences with paediatric rare diseases such as osteogenesis imperfecta,11 inherited metabolic diseases12 13 and Zellweger spectrum disorders14 from a caregivers’ perspective. In these studies, parents of affected children reported to experience concern, emotional stress and feelings of uncertainty and being overwhelmed, which stresses the need for support systems for caregivers of patients with paediatric rare diseases.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have associated children’s age or illness duration with the negative psychosocial adjustment of caregivers [ 35 , 54 , 76 ]. Furthermore, research involving family carers indicates that sleep deprivation, feelings of guilt, loneliness and isolation are closely linked to well-being and QoL [ 70 , 79 83 ]. The caregivers in this study experienced this range of emotions, which are acknowledged as stressors that impact caregivers and can, at the same time, also affect a child’s QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have associated children's age or illness duration with the negative psychosocial adjustment of caregivers [35,54,75]. Furthermore, research involving family carers indicates that sleep deprivation, feelings of guilt, loneliness and isolation are closely linked to well-being and QoL [69,[79][80][81][82][83]. The caregivers in this study experienced this range of emotions, which are acknowledged as stressors that impact caregivers and can, at the same time, also affect a child's QoL.…”
Section: Caregivers' Psychosocial and Clinical Statusmentioning
confidence: 72%